2022
DOI: 10.3390/ijerph192113776
|View full text |Cite
|
Sign up to set email alerts
|

Oral and Mucosal Complaints among Institutionalized Care Seniors in Malopolska Voivodeship—The Utility of the Mirror Sliding Test in an Assessment of Dry Mouth

Abstract: The purpose of this article was to evaluate reported oral and mucosal complaints among seniors residing in institutionalized 24-h care of the Municipal Center for Older and Dependent People (MHCOD) and the 3-month rehabilitation program of the Daily Medical Care House (DMCH). We evaluated the feasibility of using the dental mirror slidding test to assess dry mouth of seniors. Patients underwent a questionnaire, and clinical examination. The Visual Analogue Scale (VAS) was used to assess pain, Fox’s questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…A mean salivary flow rate of 0.20-0.29 ml/min was found by Van 64 Two studies estimated dry mouth by the 'adhesiveness of dental mirror on the mucosa' and found 46.0-54% of the residents experiencing moderate ('slip resistance') and 11.0-14% severe hyposalivation ('mirror trapped in mucosa'). 57,87 Very few studies reported on the prevalence of denture stomatitis. Three publications stated 10.0-15.0% of denture wearers were suffering from denture stomatitis.…”
Section: Clinical Oral Healthmentioning
confidence: 99%
See 3 more Smart Citations
“…A mean salivary flow rate of 0.20-0.29 ml/min was found by Van 64 Two studies estimated dry mouth by the 'adhesiveness of dental mirror on the mucosa' and found 46.0-54% of the residents experiencing moderate ('slip resistance') and 11.0-14% severe hyposalivation ('mirror trapped in mucosa'). 57,87 Very few studies reported on the prevalence of denture stomatitis. Three publications stated 10.0-15.0% of denture wearers were suffering from denture stomatitis.…”
Section: Clinical Oral Healthmentioning
confidence: 99%
“…8,10,30,60,61 Prevalence data on oral pain or discomfort ranged between 6.0% and 40.5%. 5,22,25,45,46,49,58,61,79,87 Considering the impact oral conditions had on the everyday lives of residents, 20.0-50.0% of residents reported their Oral Health Related Quality of Life (OHRQoL) was affected 8,41,46-48,66. Several studies reported only a mean score for the OHRQoL instrument applied 9,26,27,36,61,62,71,73,79,89 .…”
Section: Clinical Oral Healthmentioning
confidence: 99%
See 2 more Smart Citations